POSISI DAN FUNGSI TEORI SERTA LITERATUR REVIEW DALAM PENELITIAN KUALITATIF - Gusti Muhammad Alfarizi; Dina Hermina; Norlaila (As-Sulthan Journal of Education, 2025)
This research is motivated by the importance of understanding the position and function of theory as well as literature reviews in qualitative research. The problem identified is a lack of understanding and effective application of theory and literature in various types of research, which can hamper the quality of research results. The aim of this research is to analyze the role of theory and literature in supporting methodological design, data collection and qualitative interpretation of research results. This research method takes the form of an in-depth literature review, referring to various theoretical and empirical sources regarding research methodology. This research explores how theory is used inductively in qualitative research to develop contextual understanding. The research results show that theory acts as a conceptual framework that helps researchers understand phenomena and develop targeted research designs. Additionally, literature reviews serve to identify research gaps, strengthen the validity of findings, and support the development of new insights. In conclusion, good integration of theory and literature will increase the validity and contribution of research to science.